M2-2 gene as a new alternative molecular marker for phylogenetic, phylodynamic, and evolutionary studies of hRSV - Nunes, Denis Bruno S.M.; Vieira, Camila; Sá, Jéssica M. [UNESP]; Araújo, Gabriela C. [UNESP]; Caruso, Icaro P. [UNESP]; Souza, Fátima P. [UNESP] (Elsevier, 2022)
The human Respiratory Syncytial Virus (hRSV) is the main causative agent of acute respiratory infections (ARI), such as pneumonia and bronchiolitis. One of the factors that lead to success in viral replication is the interaction of the M2-2 protein with the ribosomal complex. This interaction is responsible for the phase change of viral activity, acting as an inhibitor or inducer of viral replication, according to the concentration of mRNA. Based on the importance of M2-2 gene and protein have to viral physiology, we performed here evaluations of genetic diversity, phylogenetic reconstructions, phylodynamics, and selection test. Our results suggested an alternative way of classifying this virus in clades A and B, based on a new phylogenetic marker, the M2-2 gene. Therefore, our study is the first one to investigate the dynamics of the evolutionary diversification process of hRSV from the perspective of the M2-2 viral gene. In our study was also identified that the M2-2 gene is under the effect of purifying selection originated by population genetic bottlenecks. Therefore, the M2-2 gene demonstrated an interesting potential to be applied in evolutionary studies involving hRSV, recovering phylogenetic signals and traits of natural selection under the evolution of this virus.
Keywords: Divergence time; Evolutionary dynamics; hRSV; M2-2; Molecular phylogeny; Purifying selection